2018
DOI: 10.4102/sajhrm.v16i0.907
|View full text |Cite
|
Sign up to set email alerts
|

The association between emotional intelligence and entrepreneurship as a career choice: A study on university students in South Africa

Abstract: Orientation: To examine the effects of emotional intelligence on the development of entrepreneurial intentions of university students.Research purpose: To determine whether emotional intelligence is a crucial antecedent of entrepreneurial intention to encourage entrepreneurial behaviour.Motivation of the study: By identifying all the factors that encourage entrepreneurial behaviour, policymakers and concerned stakeholders are better equipped to improve such behaviour and guarantee its success, thereby alleviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
0
16
2
1
Order By: Relevance
“…This result is in agreement with the result of a study (Sidek, & Bakar, 2020), which showed that there is a direct correlation between emotional intelligence and entrepreneurial intent. While this result differed with the result of a study (Kanonuhwa, Rungani, & Chimucheka, 2018), which showed that there is no relationship between emotional intelligence and self-efficacy in making professional decisions.…”
Section: Results Related To First Question: What Is Emotional Intelligence Level For Secondary School Students Incontrasting
confidence: 97%
“…This result is in agreement with the result of a study (Sidek, & Bakar, 2020), which showed that there is a direct correlation between emotional intelligence and entrepreneurial intent. While this result differed with the result of a study (Kanonuhwa, Rungani, & Chimucheka, 2018), which showed that there is no relationship between emotional intelligence and self-efficacy in making professional decisions.…”
Section: Results Related To First Question: What Is Emotional Intelligence Level For Secondary School Students Incontrasting
confidence: 97%
“…Social values play a vital role in determining whether or not individuals are behaving entrepreneurially (Kwon & Arenius, 2010), where researchers note that an individual's decision does not depend on his or her preferences alone but is influenced by what others in society or community choose (Bygrave & Minniti, 2000). Moreover, it is widely accepted that the entrepreneurial process has attitudinal and behavioural components, where recent studies confirm that SV together with entrepreneurial beliefs and competencies may significantly predict the innovation performance (INNP) of enterprises (Kanonuhwa, Rungani, & Chimucheka, 2018;Urban &Wood, 2017;Welter & Smallbone, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu faktor pendorong pertumbuhan kewirausahaan di suatu negara terletak pada perana perguruan tinggi melalui penyelenggaraan pendidikan kewirausahaan (Kanonuhwa et al, 2018). Pihak perguruan tinggi bertanggung jawab dalam mendidik dan memberi kemampuan wirausaha kepada para lulusannya dan memberi motivasi untuk berani memili berwirausaha sebagai karir mereka.…”
Section: A Pendahuluanunclassified